Blockade of IL-12 during the induction of collagen-induced arthritis (CIA) markedly attenuates the severity of the arthritis. - Malfait, A; Butler, D; Presky, D; Maini, R; Brennan, F; Feldmann, M (1998)
The effect of blocking IL-12, a potent inducer of interferon-gamma (IFN-gamma) and promoter of Th1 cell responses, during the induction phase of CIA was investigated. Arthritis was elicited in male DBA/1 mice by immunizing with type II collagen (CII) in Freund's complete adjuvant. Neutralizing anti-IL-12 antibodies were administered twice weekly from CII immunization. It was found that administration of anti-IL-12 from immunization until the onset of clinical arthritis did not lower the incidence of arthritis, but dramatically attenuated the severity of the disease, both clinically and histopathologically. This regime was associated with reduced IFN-gamma levels produced by ex vivo CII-stimulated draining lymph node cells, and with diminished spontaneous ex vivo production of tumour necrosis factor (TNF), IL-6 and IL-10 by freshly isolated synovial cells. Total anti-CII antibody serum levels in these mice were lower than in the controls, but there was no change in the IgG2a/IgG1 ratio. These findings confirm that IL-12 has a major role in the induction of murine CIA and suggests that this disease is propagated, in part, by cells of the Th1 phenotype.